Divergent instability control of aeroelastic system driven by aerodynamic forces under disturbance based on discrete sliding mode control algorithms - Ting-Rui Liu (Measurement + Control, 2019)
Divergent instability control of 2D pretwisted blade section of wind turbine driven by aerodynamic forces under disturbance is investigated. Realization of divergent instability control is based on two types of discrete sliding mode control algorithms. The structure is modeled as 2D pretwisted blade section integrated with structural damping, which is driven by aerodynamic model with perturbed disturbance. Discrete sliding mode control algorithm suitable for disturbance control is investigated to control divergent flap/lead-lag vibrations of blade section. To increase convergence performance and reduce the chattering phenomenon, discrete sliding mode control based on disturbance observer is applied. Convergence of disturbance observer is analyzed, and stability of closed-loop system is discussed. The simulation results show that not only the convergence accuracy can be improved by sliding mode control based on disturbance observer controller, but also the displacement chattering and the control input chattering can be effectively eliminated. Compared with conventional discrete sliding mode control, it has more advantages in the control of divergent instability. To facilitate the real-time realization and automation and at the same time to ensure accuracy, a design of quadratic feedback to build the performance control matrix in sliding mode control based on disturbance observer is developed in present study.